VALENŢELE MOTIVAŢIONALE ALE MINIMULUI DE ÎNVĂŢĂMÂNT - USM ADMIN (Moldova State University, 2008)
The realization of a performing result in the teaching / appropriation process of the Romanian language depends on motivational factors. Through these factors, the author includes the problem of organization of the minimum of education, methodically well. This minimum of education, needs to be selected and dosed so that, the students should be convinced that in a minimum unit of time an advanced degree of communication capacities in Language of the State can be achieved.